An Innovative Database of Clinical Cases to Improve the Realism of Full-Scale Exercises. (November 2022) - Crimaldi, Federico; Zulliani, M.; Porta, L.; Bortolin, Michelangelo; Merlo, Federico; Ragazzoni, Luca
Abstract : Background/Introduction: Simulation is an "educational method that can be applied to the training of processes, technical, and non-technical skills." Literature underlines how simulating with the maximum realism possible improves the quality of training. Objectives: To describe the methodology used by CRIMEDIM to create a high-quality database of clinical cases to improve the realism of the EU MODEX exercises. Method/Description: In 2021, CRIMEDIM created a new database of clinical cases with disaster and non-disaster-related injuries and diseases to be used for the EU MODEX exercises. Each clinical case has four temporal stages: prehospital, T0, T1, and T2, and each of them has two possible variations: Type A (improvement) and Type B (deterioration). Timing and treatments received (or not received) determine the evolution between one step and the following one. Each clinical case consists of past medical history, disaster-related history, drugs, and allergies. There are also various exams (eg, blood tests [blood count, ABG, biochemical test, coagulation], imaging [ultrasound, XR, CT], and EKG) and other clinical information. The database allows printing casualty cards, each containing instructions for role players and make-up artists. Results/Outcomes: At this moment, the database consists of 1, 174 clinical cases, with the possibility to create new cases according to different disaster scenarios, training needs, and learning objectives. Conclusion: According to participants' feedback, the introduction of such an innovative and comprehensive database seemed to have improved the quality and the realism of the Medical EU MODEX.